Komodifikasi Musik Resepsi Pernikahan di Bandung - Yudi Permana; Arthur S. Nalan; Indra Ridwan (Pascasarjana ISBI Bandung, 2020)
The term cover here means to re-sing or re-perform a song. The process of covering a song is essentially an adaptation, in which much of the value lies in the cover musician’s interpretation. Covers can easily be found at wedding receptions in the case of performing popular songs and romantic themes. This research studies about pop cover songs on wedding receptions, using commodification theory by Vincent Mosco. Data collection methods are literature studies, interview, and observation. From this research, the results show that the commodification of pop music covers are as follows: (1) commodification of content, cover songs are packaged into a romantic musical performance, as if giving a